Pemaknaan Regulasi Emosi pada Siswa SMP dengan Perilaku Agresif - Indah Mutiara; Indah Lestari; Wahidin (Conseils : Jurnal Bimbingan dan Konseling Islam, 2026)
This study aims to explore how junior high school students exhibiting aggressive behavior perceive and interpret emotional regulation in their daily lives. A qualitative case study approach was employed, involving students identified as having aggressive tendencies based on teacher observations and preliminary assessments. Data were collected through in-depth interviews with students, school counselors, and homeroom teachers, complemented by behavioral observations and relevant school documentation. Data analysis was conducted using a thematic approach to uncover patterns of emotional regulation and its relation to aggressive behavior. Findings reveal that students understand emotional regulation as the capacity to manage anger, control negative impulses, and express emotions adaptively. Nevertheless, its practical application is often impeded by peer pressure, classroom conflicts, and internal emotional factors such as frustration. These insights provide a nuanced understanding of students emotional management processes and serve as a foundation for developing guidance and counseling interventions, character education programs, and emotional development initiatives in schools.